Plasmon-Induced Water Splitting—through Flexible Hybrid 2D Architecture up to Hydrogen from Seawater under NIR Light; ACS Applied Materials and Interfaces; Vol. 12, iss. 25 - Guselnikova O. A. Olga Andreevna; Trelin A.; Milyutina (Miliutina) E. V. Elena Vadimovna; Elashnikov R. Roman; Sajdl P. Petr; Postnikov P. S. Pavel Sergeevich; Kolska Zh. Zdenka; Svorcik V. Vaclav; Lyutakov O. Oleksy (2020, 2020)
Title screen